2016
DOI: 10.18632/oncotarget.14024
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively staging liver fibrosis using noninvasive method in Hepatitis B virus-infected hepatocellular carcinoma patients

Abstract: BackgroundAdvanced liver fibrosis can result in serious complications (even patient’s death) after partial hepatectomy. Preoperatively percutaneous liver biopsy is an invasive and expensive method to assess liver fibrosis. We aim to establish a noninvasive model, on the basis of preoperative biomarkers, to predict liver fibrosis in hepatocellular carcinoma (HCC) patients with hepatitis B virus (HBV) infection.MethodsThe HBV-infected liver cancer patients who had received hepatectomy were retrospectively and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…And the associations between coagulation system and cancer have been frequently studied 16 . First of all, many studies have demonstrated that coagulation system has an effect on the solid tumors, such as ESCC 10 , penile cancer 17 , HCC 18 , lung cancer 11 and so on. Secondly, hematological system diseases have been reported related to this 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…And the associations between coagulation system and cancer have been frequently studied 16 . First of all, many studies have demonstrated that coagulation system has an effect on the solid tumors, such as ESCC 10 , penile cancer 17 , HCC 18 , lung cancer 11 and so on. Secondly, hematological system diseases have been reported related to this 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that prothrombin time and INR values were higher in HCC and CLD groups than controls, while no difference between HCC and CLD groups was noticed. When predicting the prognosis of cancers, coagulation parameter may be used, as solid tumors such as HCC are affected by the coagulation system (26) . A study by Goa et al (26) found that prothrombin time was higher in HCC patients than non-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…When predicting the prognosis of cancers, coagulation parameter may be used, as solid tumors such as HCC are affected by the coagulation system (26) . A study by Goa et al (26) found that prothrombin time was higher in HCC patients than non-HCC patients. A prolonged prothrombin time indicates the liver's potential for biosynthesis.…”
Section: Discussionmentioning
confidence: 99%